PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KOMITMEN ORGANISASI: PERAN MEDIASI KEPUASAN KERJA - Alvia Santoni; Gampo Heryono; Sudirman; Endri (School of Business, Bogor Agricultural University (SB-IPB), 2021)
This study aims to empirically prove the influence of leadership behavior and work environment on turnover intention with job satisfaction as a mediating variable. The research sample was conducted using purposive sampling technique and 128 non-managerial permanent employees were selected at PT. XYZ as respondent. The method for proving research hypotheses uses path analysis which can identify both direct and indirect effects and is also an indicator to test validity and reliability. The research data was processed using Partial Least Square (PLS) with SMART PLS Ver 3.0 software. The results of the study found that leadership and work environment had an effect on job satisfaction. Job satisfaction directly affects organizational commitment, while leadership and the environment indirectly through mediation of job satisfaction affect organizational commitment. Taken together, leadership, work environment, and job satisfaction determine employee organizational commitment to the company. Suggestions from the results of the study, so that employee commitment is high to the company, management needs to change leadership styles that are adaptive and transformative, as well as a comfortable and friendly work environment that can increase job satisfaction. Keywords: organizational commitment, leadership, work environment, job satisfaction, turnover intention